Age-related spatial differences of human lens UV filters revealed by negative ion mode MALDI imaging mass spectrometry. (July 2019) - Demarais, Nicholas J.; Donaldson, Paul J.; Grey, Angus C.
Abstract: Tryptophan-derived UV filters are predominantly found in the lenses of primates and humans. While protective against UV radiation, aging alters the complement and spatial distributions of human lens UV filters, and a role for UV filters has been suggested in age-related cataract formation. To establish how the spatial distributions of UV filters change in normal human lens aging, matrix assisted laser desorption/ionisation-imaging mass spectrometry (MALDI-IMS) was utilised to map the locations and relative abundance of multiple UV filters simultaneously. Frozen human lenses were cryosectioned axially, and the 20 μm-thick sections coated with MALDI matrix via robotic sprayer and analysed using negative ion mode MALDI-Fourier transform-ion cyclotron resonance MS. While signal for many UV filters was detected throughout the lenses, signal intensity was generally highest in the central (embryonic) nucleus and decreased uniformly in outer (foetal, juvenile, adult) nuclear and cortical regions, and many UV filter signals declined with age. In contrast, two antioxidant-conjugated UV filters (Cys-3-OHKG and GSH-3-OHKG) were restricted to the lens nucleus and their relative signal increased with increasing lens age. The enhanced spatial resolution of MALDI-IMS over manual trephine dissection techniques and its multiplex capability allowed the spatial relationships between lens UV filters to be established and explored in relation to aging. Together these results confirmed that the complement of UV filters in each lens is dynamic and undergoes significant age-related changes. In the future, this information could be used to compare with other lens biomolecule changes to better understand the lens aging process and age-related cataract formation.